Can Job Satisfaction be predicted by Organizational Commitment, Gender, Age, Experience, and Position? An empirical Investigation in a Private Financial Institution in Bahrain - Eleswed, Muath (2015)
Abstract The purpose of this study was to investigate whether or not job satisfaction can be predicted by organizational commitment, gender, age, experience, and position in a private financial institution in Bahrain. One hundred and fifty-six subjects participated in this study. Using a stepwise multiple regression model, results revealed that organizational commitment was the only predictor of job satisfaction. Based on the results, implications and direction for further studies were made